Reactions to an Initial Attempt At Implementing Interactive Videodisc in Extension - S. Kay Rockwell; James W. King (Journal of Applied Communications, 1988)
The study focused on evaluating (a) the computer-directed videodisc technology as a delivery method for Extension, and (b) Ihe effectiveness of using it to teach cash flow planning to farmers/ranchers. Extension agents in 12 states completed open-ended questionnaires explaining how they prepared for the videodisc and how they used it They also completed anecdotal notes on the participants. Farmer responses were recorded in a computer file when they used the program.